Book review: Ganesh Chella, Harish Devarajan and V. J. Rao, HR Here and Now: The Making of the Quintessential People Champion. Issue 2 (June 2019) - Bisht, Nidhi S.
Ganesh Chella, Harish Devarajan and V. J. Rao, HR Here and Now: The Making of the Quintessential People Champion, 2018, New Delhi: SAGE Publications, 372 pp., ₹595, ISBN: 978-93-528-0693-5.